Die Versorgungsbereichsgrenze - Wirklichkeitsfremdes Konstrukt oder Darstellung realer Sachverhalte? - Ittermann, Reinhard (ERDKUNDE, 1975)
Using the example of service linkages to higher-order central places, it is shown that settlements are oriented not to only one major central place but to a number of them. This poly-orientation, which has group-specific and goods specific causes, casts doubt on the still-valid Christaller based concept of the linearly definable spatial continuum of service linkages insofar as it is based on one central place. The concept simplifies and harmonises what is in reality a complex structure of linkages. Since settlements are simultaneously oriented to a number of higher-order centres which despite their spatial separation are complementary and should be seen as an economic unit, individual settlements can belong to the common service area of a number of towns. Service areas of this kind usually show a contiguous distribution but can have island features and exclaves.